The Effects Of Slider And Tensioner Neural Mobilization Along With Lumbar Traction Among Sciatica Patients (International Journal of Environmental Sciences, 2025)
Background: Sciatica is a condition in which there is compression over the sciatic nerve that results in pain, numbness and tingling sensation over the course of the nerve. The lumbar traction is widely used to relieve the compression. But the latest studies show that neural mobilisation is helpful in treating sciatica. It alleviates the symptoms of nerve compression and reduces pain.Methodology: In this study, 20 samples were taken under inclusion and exclusion criteria. Participants were evenly divided into 2 groups. Group A performs slider mobilisation along with traction and Group B performs tensioner mobilisation along with traction. This treatment protocol was followed 3 times per week for 2 weeks. Sciatica Bothersomeness Index (SBI) and Roland Morris Disability Questionnaire (RMDQ) were taken before and after intervention.Results: Results showed that Group A (slider neural mobilization + lumbar traction) was better than Group B (tensioner neural mobilization + lumbar traction). The statistical analysis was conducted at 95% confidence level and p < 0.0001 was considered statistically significant.Conclusion: The slider neural mobilization with lumbar traction (Group A) has reduced the symptoms and improved the activities of daily living of sciatica patients when compared to tensioner neural mobilization (Group B).